Community-Based Urban Kampong Design in Kelurahan Sorosutan, Kemantren Umbulharjo, The City of Yogyakarta - Paulus Bawole; Haryati Sutanto (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2023)
Participatory planning methodology is a method that is often used to develop urban areas, especially for low-income residential areas. Low-income community settlements, also known as urban kampong, are always exist in Indonesian urban areas, so participatory planning is very useful for developing urban kampong. In Yogyakarta, there are many urban kampongs in each sub-district area inhabited by low-income residents. One sub-district area that also has urban kampongs is Kelurahan Sorosutan, Kemantren Umbulharjo, the City of Yogyakarta. To carry out the development of urban kampong in Kelurahan Sorosutan, the KOTAKU program from Director General of Cipta Karya, Ministry of Public Works is implemented through collaborating support with several stakeholders including academics. The Urban and Residential Environment Laboratory, Faculty of Architecture and Design, Universitas Kristen Duta Wacana carried out community service in Kelurahan Sorosutan using community-based participatory planning methods. As a housing scheme, this method does not develop new houses for low-income people but carries out upgrading programs in existing kampong settlements. The involvement of students, teaching staffs, the sub-district government and the local community greatly supports the planning process. The most important stakeholder is the local community who clearly know the potential and problems they face on a daily basis. The purpose of the community service is to make a Master Plan that can be used as a reference to carry out regional development in some stages. The results obtained from this community service are the Master Plan for Regional Development Kelurahan Sorosutan, Kemantren Umbulharjo, the City of Yogyakarta.